NUT Carcinoma: Clinicopathologic Features, Molecular Genetics and Epigenetics - Moreno, Vanessa; Saluja, Karan; Pina-Oviedo, Sergio (Frontiers in Oncology, 2022)
Nuclear protein in testis (NUT) carcinoma is a rare, highly aggressive, poorly differentiated carcinoma occurring mostly in adolescents and young adults. This tumor usually arises from the midline structures of the thorax, head, and neck, and exhibits variable degrees of squamous differentiation. NUT carcinoma is defined by the presence of a NUTM1 (15q14) rearrangement with multiple other genes. In about 70-80% of the cases, NUTM1 is involved in a balanced translocation with the BRD4 gene (19p13.12), leading to a BRD4-NUTM1 fusion oncogene. Other variant rearrangements include BRD3-NUTM1 fusion (~15-20%) and NSD3-NUTM1 fusion (~6%), among others. The diagnosis of NUT carcinoma requires the detection of nuclear expression of the NUT protein by immunohistochemistry. Additional methods for diagnosis include the detection of a NUTM1 rearrangement by fluorescence in situ hybridization or by reverse transcriptase PCR. NUT carcinoma is usually underrecognized due to its rarity and lack of characteristic histological features. Therefore, the goal of this review is to provide relevant recent information regarding the clinicopathologic features of NUT carcinoma, the role of the multiple NUTM1 gene rearrangements in carcinogenesis, and the impact of understanding these underlying molecular mechanisms that may result in the development of possible novel targeted therapies.